Spații verzi urbane în sprijinul calității vieții populației - Humă, Cristina (Calitatea Vieții, 2022)
The creation of urban green spaces to improve the quality of life of the populationis highlighted in the literature and in international and national documents. This study presents the situation of the urban green space in Romania, a component of the natural environment of the city, of the urban infrastructure and a favorable element of the quality of life of the population. In this sense, the dynamics of green space surfaces in the period 2010−2019 and the green space surface belonging to an inhabitant in 2019 were analyzed, at national and city level, given the shortage of green areas, as a result (and) of their decline after1990, as well as the minimum norm provided by the Romanian legislation in force of 26 square meters of green space per capita. Also, the role and benefits of the presence of urban green spaces for the environment, communities and quality of life were shown, the current urban policies for ensuring green space in Romanian localities, as well the appreciation of urban green by the population in Romanian cities compared to European cities. In the elaboration of the paper were used statistical data from sources such as the National Institute of Statistics, the Environment Fund Administration, the European Commission and the United Nations and specialized papers were consulted, as well as strategic and legislative documents.